Introduction of List of Plant Diseases in Korea 6.1st Edition (2023 Revised Version) - Seon-Hee Kim; Jaehyuk Choi; Young-Joon Choi; Byeong-Yong Park; Su-Heon Lee; Gyoung Hee Kim; Hyun Gi Kong; Donggun Kim; Soonok Kim; Youngho Kim; Chang-Gi Back; Hee-Seong Byun; et al. (Research in Plant Disease, 2023)
More than a year has passed after the 6th edition of ‘List of Plant Diseases in Korea (LPDK)’ was published in April 2022. The 6.1st edition (2023) of List of Plant Diseases in Korea was made by correcting errors found in the 6th edition of list and adding new diseases reported after the 6th edition. There were 397 corrections from the 6th edition, most of which were simple spelling errors or minor issues. However, 12 diseases were deleted due to duplication or unclear literature proof, and 2 diseases had their diseases’ common names changed. We added 158 diseases that were reported before 2021 but not included in the 6th edition, or reported after the 6th edition. After all, 146 diseases were added to the 6,534 diseases in the 6th edition, resulting in a total of 6,680 diseases in the 6.1st edition. Thirty host taxa were also added, increasing the number from 1,390 in the 6th edition to 1,420 in the 6.1st edition. Pathogens were also added to 62 taxa, from 2,400 in the 6th edition, bringing the total to 2,462 taxa in the 6.1st edition. Ultimately, the 6.1st edition (2023) of ‘The List of Plant Diseases in Korea’ contains 6,680 diseases caused by pathogens of 2,462 taxa on 1,420 hosts. The 6.1st edition is not printed as a book, but is provided through the online ‘List of Plant Diseases in Korea’ (https://genebank. rda.go.kr/kplantdisease.do).